Advanced Heterojunction Structure of Polymer Photovoltaic Cell Generating High Photocurrent with Internal Quantum Efficiency Approaching 100%. Issue 9 (23rd May 2013) - Park, Hui Joon; Lee, Jae Yong; Lee, Taehwa; Guo, L. Jay
<x xml:space="preserve">Abstract</x> An advanced heterojunction structure is introduced for polymer photovoltaic cells that can approach almost 100% internal quantum efficiency (IQE) even with over 300 nm thick electron‐donor layer for adequate light absorption. These devices show superior charge transport properties as well as non‐Langevin type bimolecular recombination. The resultant short circuit current of the device is about 50% higher than that of the thermally annealed BHJ polymer PV cell. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>